Dissecting the Molecular Mechanism of Ionizing Radiation-Induced Tissue Damage in the Feather Follicle - Chen, Xi; Liao, Chunyan; Chu, Qiqi; Zhou, Guixuan; Lin, Xiang; Li, Xiaobo; Lu, Haijie; Xu, Benhua; Yue, Zhicao (PLOS ONE, 2014)
Ionizing radiation (IR) is a common therapeutic agent in cancer therapy. It damages normal tissue and causes side effects including dermatitis and mucositis. Here we use the feather follicle as a model to investigate the mechanism of IR-induced tissue damage, because any perturbation of feather growth will be clearly recorded in its regular yet complex morphology. We find that IR induces defects in feather formation in a dose-dependent manner. No abnormality was observed at 5 Gy. A transient, reversible perturbation of feather growth was induced at 10 Gy, leading to defects in the feather structure. This perturbation became irreversible at 20 Gy. Molecular and cellular analysis revealed P53 activation, DNA damage and repair, cell cycle arrest and apoptosis in the pathobiology. IR also induces patterning defects in feather formation, with disrupted branching morphogenesis. This perturbation is mediated by cytokine production and Stat1 activation, as manipulation of cytokine levels or ectopic Stat1 over-expression also led to irregular feather branching. Furthermore, AG-490, a chemical inhibitor of Stat1 signaling, can partially rescue IR-induced tissue damage. Our results suggest that the feather follicle could serve as a useful model to address the in vivo impact of the many mechanisms of IR-induced tissue damage.